Metode Pembentukan Pribadi Muslim Menurut Ali Abdul Halim Mahmud dalam Buku Dakwah Fardiyah - Rakhmawati, Eni (Prodi Pendidikan Agama Islam IAINU Kebumen, 2023)
Fardiyah da'wah (individual da'wah) is the effort and effort of a da'i towards someone to bring him from darkness to light, from misguidance to guidance, from lack of guidance in life to commitment to the Islamic way of life. In the process, the internalization of noble values such as fardiyah preaching has experienced a decline. This type of research uses qualitative research, with a literary (literary) approach. The primary data is the book